Constitutional Complaint as Strengthening Constitutionalism in Indonesia - Abdul Hakim Siagian (RIRAI Publisher, 2020)
The inclusion of human rights in the constitution gives a new status for these rights to become constitutional rights. The guarantee of human rights in the constitution has not been in line with legal efforts to protect these rights. Mechanisms constitutional review in Indonesia only accommodates the testing effort constitutionality of Law (judicial review), whereas there are still many objects of state action that can harm the constitutional rights of citizens, but they do not have any resolution because they have not been provided for by Indonesian positive law. This study aims to identify how the interrelationship between guaranteeing human rights in the constitution and strengthening constitutionalism due to the inclusion of human rights in the constitution, how the concept of constitutional complaints in various countries is, and how relevant is it to be applied in Indonesia. This research describes the material that exists in historical, comparative and reconstruction (modification) aspects as an effort to make the concept relevant to be applied in Indonesia. This research shows that human rights and the constitution have a reciprocal relationship (reciprocal), various concepts in other countries have a lot of relevance to Indonesia, and there are several technical-procedural concepts and juridical arrangements that are relevant to be applied in Indonesia. So, it is necessary to regulate constitutional complaints as a legal measure to protect the constitutional rights of citizens which have been guaranteed by the constitution and increase the value of the constitutionalism of citizens in Indonesia.